CURRICULUM MANAGEMENT: REALISING QUALITY LEARNING - Ali Akbarjono (International Journal of Teaching and Learning, 2025)
Effective curriculum management is the key to realising quality learning at every level of education. In this process, curriculum organisation involves thorough planning, flexible implementation and continuous evaluation. Good management ensures that teaching materials are appropriate to students' needs and able to respond to the ongoing changes in social, technological and economic contexts. Regular evaluation and critical reflection on the curriculum allows for quick and appropriate adaptation, keeping it relevant to the latest developments. This prepares students with critical thinking skills, creativity and 21st century competencies that are essential to determine their future success. Besides focusing on students, a good curriculum management strategy also strengthens parental and community involvement in the education process. Through effective communication and active participation, families and communities can support learning and fill an important role in an inclusive and conducive education ecosystem. Effective curriculum management also involves continuous professional development for teachers, ensuring that they continuously update their competencies and adopt best practices in teaching. Well-trained and motivated teachers tend to be innovative, creating dynamic learning environments and supporting improved student learning outcomes. Thus, curriculum management is the strategic foundation that ensures that every element in the educational process functions optimally to achieve superior educational quality.